Perekaman Tiga Dimensi (3D) Benda Hasil Budaya Menggunakan Telepon Pintar: Studi Kasus Arca Dewi Laksmi di Madiun - Sambodo, Goenawan A (Department of Archaeology, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
Recently, public attention for the preservation of cultural heritage has increased. This is evidenced by the increasing number of heritage enthusiasts who are actively visiting archaeological sites. However, these communities are often unaware on how they can help to preserve the cultural heritage more effectively. This article offers a participatory activity that can be carried out by the community to help preservation effort, especially in the recording and documentation of cultural heritage, namely three-dimensional (3D) recording using a smartphone. The procedure proposed here is based on a case study in recording the Lakshmi statue from Madiun. It is proven to be able to produce clear, accurate, and easy-to-use 3D recordings. As well as being able to assist the authorities in documenting cultural heritage objects, the 3D record can be used for the reconstruction of objects that are no longer complete, developed into learning materials, and dissemination of cultural heritage information quickly and easily. In this way, the community will be able to establish closer cooperation with the authorities and other parties in preserving cultural heritage. === Kepedulian masyarakat terhadap pelestarian warisan budaya sekarang ini semakin besar. Hal ini dibuktikan dengan semakin banyaknya komunitas pemerhati warisan budaya yang secara aktif mendatangi situs-situs arkeologi. Namun, tidak jarang komunitas tersebut tidak tahu bagaimana mereka dapat membantu proses pelestarian warisan budaya secara lebih efektif. Artikel ini mencoba menawarkan salah satu kegiatan partisipasi yang dapat dilakukan komunitas, khususnya dalam perekaman dan dokumentasi warisan budaya. Dokumentasi yang dimaksud adalah perekaman tiga dimensi (3D) menggunakan telepon pintar. Proses perekaman dan pengolahan data berdasarkan pada studi kasus perekaman arca Dewi Laksmi dari Madiun. Hasil perekaman arca berupa arsip digital 3D yang jelas, akurat, dan mudah dimanfaatkan. Selain dapat membantu pihak berwenang untuk mendokumentasikan warisan budaya, rekaman yang dihasilkan dapat dimanfaatkan untuk rekonstruksi benda yang sudah tidak lengkap, dikembangkan menjadi bahan pembelajaran, serta penyebaran informasi secara cepat dan mudah. Komunitas juga akan dapat menjalin kerjasama yang erat dengan pihak berwenang dalam pelestarian warisan budaya.